2000
DOI: 10.1177/135910530000500109
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stress and Mood in Sickle Cell Disease Pain

Abstract: The role of stress and mood in the onset and course of sickle cell disease (SCD) pain was examined using a daily diary design. Fifteen adults with SCD completed daily diaries about their pain, stress, mood, and health care and medication use for an average of 94 days. Multilevel random effects models indicated that stress was significantly and positively related to same-day pain ratings. Stress remained a significant predictor of pain after omitting stressors related to SCD. Mood also showed significant associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Importantly, this association was observed even after controlling for depressed affect, challenging the proposition that the apparent association between binge eating and avoidant coping is due to the confounding of avoidant coping and depression (e.g., Paxton & Diggens, 1997). Notably, distraction was the only variable in the current study that demonstrated a link with next-day binge eating, which could be considered a more robust test of causality because of the reduced risk of temporal overlap between the independent and dependent variables (e.g., Porter et al, 2000). As hypothesized, less Step 2 RS À.007 .018 À.006 .015…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, this association was observed even after controlling for depressed affect, challenging the proposition that the apparent association between binge eating and avoidant coping is due to the confounding of avoidant coping and depression (e.g., Paxton & Diggens, 1997). Notably, distraction was the only variable in the current study that demonstrated a link with next-day binge eating, which could be considered a more robust test of causality because of the reduced risk of temporal overlap between the independent and dependent variables (e.g., Porter et al, 2000). As hypothesized, less Step 2 RS À.007 .018 À.006 .015…”
Section: Discussionmentioning
confidence: 76%
“…Increased hospital services utilization has also been linked with maladaptive coping (Gil et al, 1989), somatization (typically defined as “medically unexplained symptoms”) (Sogutlu et al, 2011), somatic awareness (i.e. perception of minor bodily experiences) (McCrae and Lumley, 1998), and negative affect (NA) (McCrae and Lumley, 1998; Porter et al, 2000); positive mood has been associated with less utilization (Gil et al, 2004). Although stress was linked with hospital services use in one study (Porter et al, 2000), others failed to support this relationship (Gil et al, 2004; Porter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…perception of minor bodily experiences) (McCrae and Lumley, 1998), and negative affect (NA) (McCrae and Lumley, 1998; Porter et al, 2000); positive mood has been associated with less utilization (Gil et al, 2004). Although stress was linked with hospital services use in one study (Porter et al, 2000), others failed to support this relationship (Gil et al, 2004; Porter et al, 1998). Similarly, no association was found between catastrophizing and utilization (Citero Vde et al, 2007) or between depression (Grant et al, 2000; Levenson et al, 2008) or anxiety (Levenson et al, 2008) and health-care use in adults with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Positive affect improves resilience in managing chronic pain [28, 29]. Furthermore, positive affect may mitigate the detrimental effects of negative affect on pain [21, 3032]. The temporal stability of affect (stable vs. state) may also influence the experience of pain [18].…”
Section: Introductionmentioning
confidence: 99%